(x-1)(x-1)=(2x+1)*(x+1)-(x+3)*(x+3)

Simple and best practice solution for (x-1)(x-1)=(2x+1)*(x+1)-(x+3)*(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)(x-1)=(2x+1)*(x+1)-(x+3)*(x+3) equation:



(x-1)(x-1)=(2x+1)(x+1)-(x+3)(x+3)
We move all terms to the left:
(x-1)(x-1)-((2x+1)(x+1)-(x+3)(x+3))=0
We multiply parentheses ..
(+x^2-1x-1x+1)-((2x+1)(x+1)-(x+3)(x+3))=0
We calculate terms in parentheses: -((2x+1)(x+1)-(x+3)(x+3)), so:
(2x+1)(x+1)-(x+3)(x+3)
We multiply parentheses ..
(+2x^2+2x+x+1)-(x+3)(x+3)
We get rid of parentheses
2x^2+2x+x-(x+3)(x+3)+1
We multiply parentheses ..
2x^2-(+x^2+3x+3x+9)+2x+x+1
We add all the numbers together, and all the variables
2x^2-(+x^2+3x+3x+9)+3x+1
We get rid of parentheses
2x^2-x^2-3x-3x+3x-9+1
We add all the numbers together, and all the variables
x^2-3x-8
Back to the equation:
-(x^2-3x-8)
We get rid of parentheses
x^2-x^2-1x-1x+3x+1+8=0
We add all the numbers together, and all the variables
x+9=0
We move all terms containing x to the left, all other terms to the right
x=-9

See similar equations:

| f(-2)(0)=-5^2-20 | | 1^5x+2=243 | | -7/2+2/7u=-8/3 | | (2x–3)=(13x–41)=180 | | (-2)(x)=-5^2-20 | | 3^(2x)=17 | | -6.7=b-2.5 | | 1-6x=3/2x+7 | | −18+5z=37 | | 3.1*x=55.8 | | m-7=-19 | | 0.12x=3.36 | | /115=25y | | 2x=2x+67 | | 7*3^(x)=189 | | (x+5)^2+x^2=25^2 | | -4(-1-6x)=148 | | x+1/2=x-8 | | p+324/31=15 | | x*x=(x-2)*(x+4) | | 6z-1=3 | | n+234/30=12 | | 2xx20=90 | | 3535=17251725÷h | | Y=38(0.29)^x | | 26+5r=71 | | x+5/2x+1=1 | | 13=4/k+9 | | 5x+13+3x+33=79 | | 0.2n=-4 | | j-758/11=12 | | 8=1h |

Equations solver categories